Corporate tax, capital structure, and the accessibility of bank loans: Evidence from China - WU, Liansheng (Institutional Knowledge at Singapore Management University, 2009)
In this paper, we investigate whether listed firms in China adjust their capital structure in response to an increase in the corporate taxrate. Although theories of capital structure suggest that corporate tax is an important determinant of capital structure, how exogenouschanges of the tax rate affect firms’ leverage decisions has not been fully explored. We examine a unique circumstance in which the Chinesegovernment increased the corporate tax rate of firms that had previously received local government tax rebates. The evidence indicatesthat these firms increased their leverage when the corporate tax rate increased. Further investigation suggests that the adjustment ofleverage was mostly driven by firms with a high level of access to bank loans.